Struktur dan Fungsi Sosial Nyanyian Rakyat Lullaby Senandung Mendindong Anak Masyarakat Kampung Padang Jorong Salido Barat Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Putri, Fauziah; Zulfadhli, Zulfadhli (TSAQOFAH, 2026)
Oral literature lives and develops within traditional communities that are not yet oriented toward written culture, one manifestation of which is lullaby folk songs that function both to put children to sleep and to transmit cultural values. This study aims (1) to describe the structure of the lullaby folk song Senandung Mendindong Anak in the community of Kampung Padang Jorong Salido Barat, Lembah Melintang Subdistrict, Pasaman Barat Regency and (2) to describe the social functions of this folk song. The research employed a descriptive-analytical method by first describing the lullaby textually, then analyzing its physical and inner structures, and interpreting its social functions. The physical structure examined includes typography (lines and stanzas), diction, imagery (visual and kinesthetic), concrete words, figurative language, and versification (rhyme and rhythm), while the inner structure encompasses theme, emotion, tone, and message. The findings show that Senandung Mendindong Anak is characterized by a simple, repetitive, and rhythmic physical structure, with diction, imagery, and figurative language that reinforce an atmosphere of tenderness and emotional closeness between mother and child, and an inner structure centered on themes of affection, protection, and parents’ hopes for their children’s future. The social functions of this folk song are identified as a system for projecting parental feelings and aspirations, a medium of child education through the inculcation of moral and cultural values, and a recreational vehicle that creates a calming atmosphere within the family environment. These findings affirm that traditional lullabies function not only as entertainment, but also as media for preserving cultural values and identity in the life of the local community.